GROUPING OF ADMINISTRATIVE RAIONS IN KYIV OBLAST BASED UPON SOCIODEMOGRAPHIC INDICATORS USING CLUSTER ANALYSIS - BARAN, Ganna (Ekonomichna ta Sotsialna Geografiya, 2015)
A grouping of administrative raions in Kyiv oblast was conducted based upon a number of socio-demographic indicators and using the method of cluster analysis. Cluster analysis allowed identifying two clusters of Kyiv oblast administrative raions and three sub-clusters within each of them. Inherent features of the socio-demographic development have been identified for each cluster and sub-cluster of administrative raions. The map based on the results of the analysis gives the opportunity to establish the existence of territorial patterns in the placement of certain groups of administrative raions with similar socio-demographic development in Kyiv oblast.

Здійснено групування районів Київської області за рядом соціально-демографічних показників із використанням методу кластерного аналізу. Кластерний аналіз дав змогу виділити у межах Київської області два кластери районів, у межах кожного з яких виділено по три підкластери. У межах кожного кластеру та підкластеру було визначено особливості соціально-демографічного розвитку, що їм притаманні та вирізняють серед інших груп районів. Побудована за результатами аналізу картосхема дає можливість встановити наявність територіальних закономірностей у розміщенні певних груп районів зі схожим соціально-демографічним розвитком у межах Київської області.
ГРУПУВАННЯ РАЙОНІВ КИЇВСЬКОЇ ОБЛАСТІ ЗА СОЦІАЛЬНО-ДЕМОГРАФІЧНИМИ ПОКАЗНИКАМИ З ВИКОРИСТАННЯМ КЛАСТЕРНОГО АНАЛІЗУ
Keywords: socio-demographic development; сluster analysis; Kyiv oblast; соціально-демографічний розвиток; кластерний аналіз; Київська область